Lamellar body count as a predictor of neonatal respiratory distress syndrome in preterm premature rupture of membranes - Arora, Sheetal; Chauhan, Varsha; Rana, Deepshikha; Dhupia, J. S.; Mandal, A. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Lamellar bodies are present in amniotic fluid and their quantity increases with increased gestational age. Preterm premature rupture of the membranes (P-PROM) is one of the most common complications of pregnancy and is a major cause of preterm deliveries and thus the important cause of RDS. Fetal pulmonary maturity can be assessed by direct or indirect measurement of surfactant phospholipids secreted by the fetal lungs into amniotic fluid. Lamellar body count (LBC) has been introduced as an alternative to other methods. Methods: The study’s prime aim is to establish LBC as a predictor of RDS in P-PROM. We included pregnant women with P-PROM and gestational age between 28 weeks and 37 weeks and singleton live pregnancy. The lamellar body counting from amniotic fluid was done with the use of a standard hematology cell counter, sysmex KX-21. There was statistically significant co-relation between lamellar body count and period of gestation (by applying ANOVA). Results: Lamellar body counts were significantly less in cases of RDS as compared to non RDS cases. Conclusions: LBC count was selected among all other tests because the test can be performed with equipment found in most clinical analysis laboratories and is reliable in predicting fetal lung maturity.